Synthesis, structural studies and ligand influence on the stability of aryl-NHC stabilised trimethylaluminium complexes1. Issue 34 (14th September 2015) - Wu. M, Melissa; Gill, Arran M.; Yunpeng, Lu; Falivene, Laura; Yongxin, Li; Ganguly, Rakesh; Cavallo, Luigi; García, Felipe
<x xml:space="preserve">Abstract</x> Treatment of a series of aromatic NHCs with trimethylaluminium produced their corresponding NHC·AlMe3 adducts displaying different stabilities. Their stabilities are rationalized using topographic steric maps and NHC % V Bur.